Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs